Planning for a Resilient Open Space: A Comparative Study on the Driving Forces and Spatial Effects of Urbanization in Flanders - Tempels, Barbara; Verbeek, Thomas; Pisman, Ann; Allaert, Georges (AESOP, 2012)
This paper examines the resilience of open space in Flanders, a highly urbanized region facing increasing pressure from fragmentation and changing land use. Through a comparative study of nine municipalities, the research analyses four major functions—residential, economic, private, and recreational—that shape the transformation of open space. Results show that while peripheral areas retain resilience through strong agricultural production, suburban areas have crossed thresholds into new regimes dominated by urban needs. The study highlights the role of new users and functions in influencing resilience and calls for policies adapted to regional differences and evolving spatial dynamics.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: open space; urbanization; spatial transformations; regional differences; driving forces; resilience